Edaphological, topographic and climate characterization of the main wine-growing regions of the province of Catamarca in Argentina - Babelis, German Claudio; Bueno Grimalt, Luis Anibal; Schulz, Guillermo; Tapia, Esteban Raul; Delfino, Angel Emanuel; Moreiras, Stella Maris; Flores Cáceres, María Laura (Facultad de Ciencias Agrarias, Universidad Nacional de Cuyo, 2024)
Poster